If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4a + -7) = 0 Reorder the terms: 3(-7 + 4a) = 0 (-7 * 3 + 4a * 3) = 0 (-21 + 12a) = 0 Solving -21 + 12a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 12a = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 12a = 0 + 21 12a = 0 + 21 Combine like terms: 0 + 21 = 21 12a = 21 Divide each side by '12'. a = 1.75 Simplifying a = 1.75
| 10x+(8x+12)=19x+10 | | 2x+18=4x-2 | | 8x+16=14x-14 | | 7a/2=15 | | 42-0.125Q=10+.075Q | | 2W^2+8W-42-W^2-7W-198=0 | | -2a^2+12b+7=0 | | 6-+8= | | -54/6= | | -12/-4= | | (7x-12)-(7x-11)=1 | | 4--9+-7= | | a/26-5.5v2a=9/13+20a/13+4/13 | | 147-7x=29x+23 | | 0=6x^2+12x-594 | | -11x=-7 | | 602-67x=53xk | | 23/k+1=4 | | 2+x+5/4=x+1 | | -3(x-5)+5(x+7)+22=82 | | 2x+5x=13 | | 160-5x=40x+20 | | 3x+14=-27-7x | | 82-2x=16x+20 | | b^2-11n+24=0 | | 2x+22=12x-88 | | -24-2x=3x+6 | | (x+6)+13=3x+15 | | 7x+16=6x+18 | | 15x-16=(10x)+(4x+1) | | 3-x/4=-1 | | (9x-5)+(5x-1)=13x+7 |